Arthroscopic Bone Grafting of Deep Acetabular Cysts Using a Curved Delivery Device - Garabekyan, Tigran (Arthrosc Tech, 2016)
Acetabular intraosseous cysts are frequently encountered in patients with dysplasia or femoroacetabular impingement. Small cysts are typically addressed by removing the cyst lining and stimulating healing via microfracture or abrasion chondroplasty. In contrast, larger cysts involving 1-3 cm(3) frequently require additional fortification with bone graft material to facilitate osseous ingrowth and cyst healing. Previous arthroscopic reports have described the use of rim trimming to access the extra-articular side of the cyst, with subsequent use of straight metal cannulas for delivery of bone graft material. The downsides of this technique include the requirement for rim trimming, which may be ill advised in patients with normal coverage or dysplasia, as well as the creation of a second breach in the cyst wall, precluding pressurization of the bone graft material. We describe an arthroscopic technique using a curved delivery device allowing for deeper penetration into the cyst cavity through the articular side and greater delivery of bone graft material.